2016
DOI: 10.3892/mmr.2016.6080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycium barbarum polysaccharides on the damage to human endometrial stromal cells induced by hydrogen peroxide

Abstract: Previous studies have shown that Lycium barbarum polysaccharides (LBPs) serve an important role in antioxidant activity to protect the cells and tissues. However, the specific mechanism of LBPs in the prevention of endometrial damage remains to be elucidated. Using morphological observation, cell proliferation assay, the detection of superoxide dismutase (SOD) activity and the content of malondialdehyde (MDA) in cell culture supernatant fluid, the detection by western blot analysis and reverse transcription-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The cytotoxicity of H 2 O 2 is related to oxidative stress and is mainly characterized by an increase in reactive oxygen and the disruption of antioxidant defense, which leads to a decrease in cell viability [ 13 , 32 ]. According to our results, H 2 O 2 affected cell viability in a time-dependent and dose-dependent manner, which is consistent with the results of previous studies [ 21 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of H 2 O 2 is related to oxidative stress and is mainly characterized by an increase in reactive oxygen and the disruption of antioxidant defense, which leads to a decrease in cell viability [ 13 , 32 ]. According to our results, H 2 O 2 affected cell viability in a time-dependent and dose-dependent manner, which is consistent with the results of previous studies [ 21 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a key factor of the cellular oxidative stress cascade, H 2 O 2 is considered an important component in placental oxidative ischemia/reperfusion stress. LBP has been reported to protect the testes from high-temperature injury, and improve immune ability and oxidative free radical resistance ( 27 ). However, whether LBP reduces H 2 O 2 -induced injury in trophoblast cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al [35] found that alloxan caused an obvious decrease in the SOD activity and increase in the MDA level; such effects were inhibited by Lycium barbarum polysaccharide (LBP), indi-cating that it exerted protection against alloxan-induced isolated rat islet ceus damage. Sheng et al [36] showed that pretreatment of rat pheochromocytoma (PC12) cells with 7 Oxidative Medicine and Cellular Longevity activity of SOD; LBPs also increased Bcl-2 expression and decreased caspase-3 expression [37]. Moreover, LBPs can protect mouse testicular cells against heat-induced injury and H 2 O 2 -induced DNA injury by improving the SOD activity [38].…”
Section: Discussionmentioning
confidence: 99%